2016
DOI: 10.1038/hr.2016.37
|View full text |Cite
|
Sign up to set email alerts
|

Effects of xanthine oxidase inhibitors on renal function and blood pressure in hypertensive patients with hyperuricemia

Abstract: Hyperuricemia may promote the progression of hypertension and renal dysfunction. However, the effects of hyperuricemia treatment on blood pressure and renal function in adult hypertensive patients with hyperuricemia remain unclear. A total of 137 hypertensive patients with hyperuricemia (96 men and 41 women; mean age of 67 years) who recently started taking xanthine oxidase inhibitors (allopurinol or febuxostat) as outpatients were recruited. Serum uric acid level, estimated glomerular filtration rate (eGFR, m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(19 citation statements)
references
References 29 publications
0
18
0
1
Order By: Relevance
“…Although previous studies failed to show that SUA lowering or xanthine oxidase inhibition slows the progression of renal dysfunction 36) or reduces cardiovascular risk, 37) further investigations are required before we can make any definitive conclusions concerning the use of different classes of SUA-lowering drugs, such as new non-purine xanthine oxidase inhibitors, and the measurement of multiple outcomes, some of which are ongoing. [38][39][40][41][42] In summary, SUA was found to be associated positively with LVMI and BNP, and negatively with LVEF in both genders. However, after taking diuretic use into consideration in the statistical model, association between SUA and LVEF among male patients and that between SUA and LVEF or BNP among female patients lost statistical significance.…”
Section: Discussionmentioning
confidence: 99%
“…Although previous studies failed to show that SUA lowering or xanthine oxidase inhibition slows the progression of renal dysfunction 36) or reduces cardiovascular risk, 37) further investigations are required before we can make any definitive conclusions concerning the use of different classes of SUA-lowering drugs, such as new non-purine xanthine oxidase inhibitors, and the measurement of multiple outcomes, some of which are ongoing. [38][39][40][41][42] In summary, SUA was found to be associated positively with LVMI and BNP, and negatively with LVEF in both genders. However, after taking diuretic use into consideration in the statistical model, association between SUA and LVEF among male patients and that between SUA and LVEF or BNP among female patients lost statistical significance.…”
Section: Discussionmentioning
confidence: 99%
“…If there is a role for XO and/or hyperuricemia on CKD progression remains contradictory. One recent study by Kohagura et al, in 137 patients with hypertension and hyperuricemia who started treatment with XO inhibitors, showed a, albeit modest, protective effect on renal function in hypertensive patients [74].…”
Section: Xanthine Oxidasementioning
confidence: 98%
“…In a retrospective cohort study of 803 CKD patients, propensity score analysis using three different methods showed a consistent impact of high UA on progression to end-stage renal disease (ESRD) [118]. XO inhibitors possibly delay the progression of CKD in adult hyperuricemic and hypertensive patients [119]. The target SUA should be <6.5 mg/dL to delay progression [77], [118].…”
Section: Uric Acid and The Kidneymentioning
confidence: 99%